Role of complementary therapies in the understanding of primary healthcare professionals: a systematic review - Mariana Cabral Schveitzer; Elma Lourdes Campos Pavone Zoboli (SciELO, 2014)
Objective To identify the understanding of the healthcare professionals in relation to the role of complementary therapies in primary health care. Method Systematic review by way of the following information sources: PubMed, CINAHL, PeriEnf, AMED, EMBASE, Web of Science, Psicoinfo and Psicodoc, using the keyword Primary Health Care alone, and associated with the following keywords: Medicinal Plants, Herbal Medicine, Homeopathy, Traditional Chinese Medicine, Acupuncture, Anthroposophical Medicine. Results Twenty-two studies from 1986 to 2011 were included. We identified three styles of practice: conventional medicine, complementary therapies and integrative medicine. Positioning professional practices within these three styles may facilitate discussion of concepts of health care, enhancing the health care provided as a result. Conclusion The work process in primary care presents difficulties for conducting integrative and holistic health care, but this practice has been introduced over time by professionals who integrate conventional medicine and complementary therapies, concerned with the care and well-being of patients.